2010
DOI: 10.1007/s11355-010-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of allochthonous sediment and litter on a sediment bar subject to sand release from an upstream dam

Abstract: Release of trapped sediment from a dam is currently considered to be an effective mitigation method in dammed rivers. However, it has a high impact on the ecosystems downstream. In order to mitigate the impact of the sediment trapped by these dams, sediment gates were constructed in the two most downstream dams-Dashidaira Dam and Unazuki Dam-to release trapped sediment into the downstream. Since synchronous sediment release from Dashidaira Dam and Unazuki Dam was initiated, however, the formerly completely sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although flow regulation has been connected to the reduced vegetation in river floodplains in many cases (Stromberg et al ., ; Coble and Kolb, ; Coble and Kolb, ), we have observed that stabilized flow regimes have led to the colonization of woody and herbaceous vegetation in downstream river channels and floodplains in several Japanese rivers (Azami et al ., ; Asaeda et al ., ; Gomes and Asaeda, ; Asaeda et al ., ). The downstream area of the Kurobe River, Japan, became vegetated since the beginning of sediment release from two of its most downstream dam in the early 1990s (Tazaki et al ., ; Sakamoto et al ., ; Asaeda and Rashid, ). Asaeda and Rashid () reported that the encroachment of herbaceous vegetation on the floodplain of the Kurobe River was due to the improved soil moisture and nutrient concentrations of soil.…”
Section: Introductionmentioning
confidence: 99%
“…Although flow regulation has been connected to the reduced vegetation in river floodplains in many cases (Stromberg et al ., ; Coble and Kolb, ; Coble and Kolb, ), we have observed that stabilized flow regimes have led to the colonization of woody and herbaceous vegetation in downstream river channels and floodplains in several Japanese rivers (Azami et al ., ; Asaeda et al ., ; Gomes and Asaeda, ; Asaeda et al ., ). The downstream area of the Kurobe River, Japan, became vegetated since the beginning of sediment release from two of its most downstream dam in the early 1990s (Tazaki et al ., ; Sakamoto et al ., ; Asaeda and Rashid, ). Asaeda and Rashid () reported that the encroachment of herbaceous vegetation on the floodplain of the Kurobe River was due to the improved soil moisture and nutrient concentrations of soil.…”
Section: Introductionmentioning
confidence: 99%